2018
DOI: 10.1016/j.econlet.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Measuring international uncertainty: The case of Korea

Abstract: We leverage a data rich environment to construct and study a measure of macroeconomic uncertainty for the Korean economy. We provide several stylized facts about uncertainty in Korea from 1991M10-2016M5. We compare and contrast this measure of uncertainty with two other popular uncertainty proxies, financial and policy uncertainty proxies, as well as the U.S. measure constructed by Jurado et al. (2015).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 12 publications
(7 reference statements)
2
16
0
Order By: Relevance
“…Sum (2012a) and Sum (2012b) for the Euro zone, Croatia, Norway, Russia, Switzerland, Turkey, and Ukraine, Bhagat et al (2013) for India, Antonakakis et al (2013), Kang and Ratti (2013) for the US, found a negative causal relationship between EPU and the stock returns. The significant negative effect of the EPU on stock returns also finds support from the empirical studies of Boudoukh et al (2012), Antonakakis et al (2013), Brogaard and Detzel (2015), Davis (2016), Demir and Ersan (2016), Bayar and Erem Ceylan (2017), Shin et al (2017) and Baker et al (2018). However, Brogaard and Detzel (2015) concluded that higher EPU leads to lower contemporaneous stock returns but results in higher future returns.…”
Section: Theory and Literature Reviewmentioning
confidence: 53%
“…Sum (2012a) and Sum (2012b) for the Euro zone, Croatia, Norway, Russia, Switzerland, Turkey, and Ukraine, Bhagat et al (2013) for India, Antonakakis et al (2013), Kang and Ratti (2013) for the US, found a negative causal relationship between EPU and the stock returns. The significant negative effect of the EPU on stock returns also finds support from the empirical studies of Boudoukh et al (2012), Antonakakis et al (2013), Brogaard and Detzel (2015), Davis (2016), Demir and Ersan (2016), Bayar and Erem Ceylan (2017), Shin et al (2017) and Baker et al (2018). However, Brogaard and Detzel (2015) concluded that higher EPU leads to lower contemporaneous stock returns but results in higher future returns.…”
Section: Theory and Literature Reviewmentioning
confidence: 53%
“…To the best of our knowledge, the only applications for developed countries in the literature are Grimme and Stöckli ( 2018 ) for Germany and Shin et al. ( 2018 ) for South Korea. For larger developing economies, the only references are Huang et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shin et al. ( 2018 ) estimate the JLN uncertainty index for South Korea, which has similar dynamics with the Korean analog of the US VIX (denominated VKOSPI), but not with the EPU index. Regarding the effect of macroeconomic uncertainty on economic activity, the Korean indicator of industrial production falls sharply about 1% when uncertainty increases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, we control the effect of the Korean economic uncertainty and investigate whether previous findings are robust to it. Specifically, we additionally include the Korean uncertainty index constructed by Shin et al (2018) 12 in Eq. (1) to estimate the marginal effects of the US economic uncertainty ( ) and the Korean economic uncertainty ( ).…”
Section: Robustness Checkmentioning
confidence: 99%
“…We appreciate an anonymous referee to suggest robustness tests using the Korean uncertainty index and the VIX.12 The Korean economic uncertainty index constructed byShin et al (2018) is provided as Appendix A. Supplementary…”
mentioning
confidence: 99%